Fulminant Reversible Cerebral Vasoconstriction Syndrome: The Other Thunderclap Headache - Brown, Keith A; Brady, James; Alimam, Ammar (Global Journal of Medical and Clinical Case Reports, 2020)
Reversible Cerebral Vasoconstriction Syndrome (RCVS) is a rare neurologic clinical syndrome that is often misdiagnosed. The pathophysiology of RCVS is unknown, but oftentimes presents as a thunderclap headache that is commonly overlooked once cerebral hemorrhage is ruled out of the differential. Typically patients follow a benign course and make a full recovery, however, in a small subset of patients RCVS can result in permanent neurologic damage. We present a patient with an uncommon clinical course of RCVS and identify pitfalls in the diagnostic workup.